2016
DOI: 10.1017/s0022215116008100
|View full text |Cite
|
Sign up to set email alerts
|

Survival and quality of life in oropharyngeal cancer patients treated with primary chemoradiation after salivary gland transfer

Abstract: The treatment delay associated with salivary gland transfer surgery does not negatively affect patient survival. Oropharyngeal squamous cell patients have an excellent quality of life after salivary gland transfer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 30 publications
0
9
1
Order By: Relevance
“…Median time to primary treatment (surgical or nonsurgical) in our cohort was 42 days overall (32 days in primary surgery group, 46.5 days in nonsurgical group). Notably, the median time to treatment in our cohort was 26 days faster than that reported in another SMGT cohort by Morand et al 22 Graboyes et al examined over 40 000 patients in the NCDB with HNC undergoing postoperative RT from 2006 to 2014, and found that administration of adjuvant RT >6 weeks after surgery was associated with 10% worse overall 5-year survival. 27 Delay in administration of adjuvant radiation occurred in 55% of cases reported by Graboyes et al By comparison, 32% of our surgical patients (6/19) had a delay in adjuvant radiation start time more than 6 weeks after surgery, a relative improvement of 31%.…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…Median time to primary treatment (surgical or nonsurgical) in our cohort was 42 days overall (32 days in primary surgery group, 46.5 days in nonsurgical group). Notably, the median time to treatment in our cohort was 26 days faster than that reported in another SMGT cohort by Morand et al 22 Graboyes et al examined over 40 000 patients in the NCDB with HNC undergoing postoperative RT from 2006 to 2014, and found that administration of adjuvant RT >6 weeks after surgery was associated with 10% worse overall 5-year survival. 27 Delay in administration of adjuvant radiation occurred in 55% of cases reported by Graboyes et al By comparison, 32% of our surgical patients (6/19) had a delay in adjuvant radiation start time more than 6 weeks after surgery, a relative improvement of 31%.…”
Section: Discussioncontrasting
confidence: 46%
“…21 SMGT results in significantly better xerostomia scores compared with IMRT as well. 22 A systematic review and meta-analysis concluded that, overall, SMGT prevents xerostomia in 83% of patients. 23 Oncologic outcomes are available for a small number of patients.…”
Section: Introductionmentioning
confidence: 99%
“…10,[26][27][28][29][30] However, with the aid of SMG-T, previous reports have shown that mean radiation doses from 23 to 30.86 Gy could routinely be achieved, and reports of moderate to severe xerostomia were low, between 11% and 31.6% (Table 4). [31][32][33] Oncologic safety must be maintained as a priority during these procedures. When patients undergo SMG-T, the specimen should be sent for pathologic analysis to make sure that there are not neck micrometastasis in level Ia and contralateral level Ib which are scheduled for sparing from subsequent IMRT.…”
Section: Discussionmentioning
confidence: 99%
“…With the intensification of nonoperative treatment approaches, an increasing number of patients are experiencing long-term swallowing impairments and functional deficiencies 38 . These late toxic effects are more common following primary chemoradiation in comparison to upfront surgery with postoperative radiotherapy 38,39 . Tschiesner et al .…”
Section: Discussionmentioning
confidence: 99%